Cell-in-cell phenomena in cancer. Issue 12 (December 2018) - Fais, Stefano; Overholtzer, Michael
Abstract Cell-in-cell structures are reported in numerous cancers, and their presence is an indicator for poor prognosis. Mechanistic studies have identified how cancer cells manage to ingest whole neighbouring cells to form such structures, and the consequences of cell-in-cell formation on cancer progression have been elucidated. In this Opinion article, we discuss how two related cell-in-cell processes, cell cannibalism and entosis, are regulated and how these mechanisms promote cancer progression. We propose that cannibalistic activity is a hallmark of cancer that results in part from selection by metabolic stress and serves to feed aggressive cancer cells. This Opinion describes cell-in-cell processes in cancer, providing insight into their functional purpose in tumour tissue. Entosis is a unique process in which cancer cells are actively invaded by other cells, conferring them a competitive advantage that may drive cancer evolution.